Shah Wali Allah al-Dihlawi and the Conclusive Argument from God - Chowdury, Saeyd Rashed Hasan (UIN Sunan Gunung Djati Bandung, 2024)
This scholarly analysis critically assesses the literary work, “The Conclusive Argument From God: Hujjat Allah al-Baligha,” by Shah Wali Allah al-Dihlawi. Dihlawi’s Hujjat Allah al-Balighah delved into the intricacies of Sharia by unveiling its underlying principles and exploring its various branches. While grounded in Sharia’s esoteric dimensions, the work seamlessly integrates Hadith, Fiqh, ethical teachings, Sufism, and even philosophical elements. Drawing upon his expertise in descriptive and epistemological disciplines, Dihlawi navigated these mysteries with an unwavering commitment to knowledge. Remarkably, he identified the scientific justification for each Quranic and Prophetic mandate, bridging the gap between revelation and reason. Furthermore, he eloquently emphasized the importance of Sufism and spirituality within the Islamic context. Hujjat Allah al-Balighah illuminated the relevance and interconnectivity of the four primary Sunni schools of thought, highlighting their joint base in Islamic law and tradition.